(untitled) (Journal of Telenursing (JOTING), 2024)
This study analyzes the relationship between body mass index and physical activity with hypertension in the Kemayoran Health Center work area. The method used is a cross-sectional design. The study results showed a p-value of 0.020 on the BMI variable and 0.045 on the physical activity variable. In conclusion, a significant relationship exists between body mass index (BMI) and hypertension and between physical activity and hypertension in the Kemayoran Health Center work area. Keywords: Physical Activity, Hypertension, Body Mass Index (BMI)